TOLERANSI DALAM ISLAM - Jamil Jamil (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2018)
Tolerance is an attitude that needed by people how to live in peace and love in the society which is different in culture, religion, social economy and soon. There is no word tolerance founded in the al-Qur`an, but explicitly, al-Qur`an explained the idea of tolerance that related to the Islamic teaching and the norm that used by muslim people to live side by side in the society which is different in religion, culture, and social economy